P569 Online education significantly improved gastroenterologists' knowledge of management strategies and treatment options for ulcerative colitis. (27th May 2021) - Bell, E; Calle, M
Abstract: Background: Ulcerative colitis (UC) is a challenging condition for gastroenterologists to manage. With the rapid evolution of the treatment landscape and more stringent goals for therapy, many physicians may struggle to stay abreast of current best practice in UC management. We assessed whether online continuous medical education (CME) can improve gastroenterologists' knowledge of management strategies and treatment options for UC. Methods: Gastroenterologists participated in an online CME activity entitled 'Key Considerations for Treatment Success in Patients With UC'. This was a 45-minute segmented video activity with accompanying slides. Questions were developed to address each of the educational objectives for the activity. Educational effect was assessed using a repeated-pair design, pre-/post-assessment. A Chi-square test of independence determined if a statistically significant improvement (5% significance level, P <.05) existed in the number of correct responses between the pre-test and post-test scores. Cramer's V estimated the effect size of the education (<.06, modest impact; .06-.15, noticeable impact; .16-.26, considerable impact; >.26, extensive impact). The activity launched on 16 May 2019 with data collection through 11 September 2019. Results: A total of 1173 gastroenterologists participated in the activity. Of those, 171 completed both pre- and post-questions, providing a set of linked learner data for analysis. The results showed: Significant improvement in average percentage of correct responses, rising from 47% at baseline to 77% post-activity ( P <.001) and extensive educational impact (Cramer's V=.260) The percentage of gastroenterologists (n=171) answering all 3 questions correctly more than tripled, from 13% pre-activity to 41% post-activity Significant improvements in knowledge of UC pathogenesis, treatment targets according to STRIDE recommendations, and which drug targets IL-12 and IL-23 ( P <.001 for all 3 questions) 38% of gastroenterologists reported increased confidence in selecting an appropriate therapy for a patient with UC Conclusion: Online education significantly improved gastroenterologists' knowledge of management strategies and treatment options in UC which should support them in achieving successful outcomes for their patients. However, there remains a notable gap in knowledge of the STRIDE recommendations and in confidence regarding treatment selection. These results suggest that gastroenterologists would benefit from additional education to reinforce their knowledge of UC management strategies and improve their confidence in translating these principles into clinical practice.